Activity-based proteomics reveals nine target proteases for the recombinant protein-stabilizing inhibitor SlCYS8 in Nicotiana benthamiana - Jutras, P; Grosse-Holz, F; Kaschani, F; Kaiser, M; Michaud, D; Van Der Hoorn, R (Wiley, 2019)
Co-expression of protease inhibitors like the tomato cystatin SlCYS8 is useful to increase recombinant protein production in plants, but key proteases involved in protein proteolysis are still unknown. Here, we performed activity-based protein profiling to identify proteases that are inhibited by SlCYS8 in agroinfiltrated Nicotiana benthamiana. We discovered that SlCYS8 selectively suppresses papain-like cysteine protease (PLCP) activity in both apoplastic fluids and total leaf extracts, while not affecting vacuolar-processing enzyme and serine hydrolase activity. A robust concentration-dependent inhibition of PLCPs occurred in vitro when purified SlCYS8 was added to leaf extracts, indicating direct cystatin-PLCP interactions. Activity-based proteomics revealed that nine different Cathepsin-L/-F-like PLCPs are strongly inhibited by SlCYS8 in leaves. By contrast, the activity of five other Cathepsin-B/-H-like PLCPs, as well as 87 Ser hydrolases, was unaffected by SlCYS8. SlCYS8 expression prevented protein degradation by inhibiting intermediate and mature isoforms of granulin-containing proteases from the Resistant-to-Desiccation-21 (RD21) PLCP subfamily. Our data underline the key role of endogenous PLCPs on recombinant protein degradation and reveal candidate proteases for depletion strategies.